2015
DOI: 10.1039/c4an01779j
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of agglutination strength by a flow-induced cell movement assay based surface plasmon resonance (SPR) technique

Abstract: A flow-induced cell movement assay combined with a surface plasmon resonance (SPR) technique was developed to quantify the agglutination strength, derived from the standard tube-agglutination test. Red blood cells (RBCs), based on the ABO blood group system, were specifically captured by anti-A and/or anti-B antibodies immobilized on a sensor surface. The agglutination strength corresponds to the amount of antigen-antibody interactions or the strength of RBC adhesion. Under a shear flow, the adherent RBCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Generally, RBC antigen-specific IgM or IgG antibodies immobilized on the surface of SPR can be used to identify blood groups (71,72). The intensity of agglutination depends on RBC adhesion and wall shear stress (73). The adhered RBCs move at different average cell velocities under the shear flow, which produces resistance.…”
Section: Surface Plasmon Resonance Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, RBC antigen-specific IgM or IgG antibodies immobilized on the surface of SPR can be used to identify blood groups (71,72). The intensity of agglutination depends on RBC adhesion and wall shear stress (73). The adhered RBCs move at different average cell velocities under the shear flow, which produces resistance.…”
Section: Surface Plasmon Resonance Testingmentioning
confidence: 99%
“…Higher average cell velocity decreases the resistance of antigen and antibody binding and lowers agglutination intensity. The antigen density of A 1 and B RBCs from that of A 1 B RBCs and can be resolved using this approach (73).…”
Section: Surface Plasmon Resonance Testingmentioning
confidence: 99%
“…Houngkamhang et al [27] reported ABO blood typing via SPR imaging which observed interaction between immobilized Anti-A and Anti-B antibodies array and A and B antigens on RBCs surface. The interaction of antigens around lower RBCs membrane surface and immobilized Anti-A and Anti-B antibodies array was applied to obtain the agglutination strength of the RBCs and immobilized antibody [28]. The SPR imaging, which utilized the shear force generated within the flow cell, was used to measure the rolling speed of red blood cell [28].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of antigens around lower RBCs membrane surface and immobilized Anti-A and Anti-B antibodies array was applied to obtain the agglutination strength of the RBCs and immobilized antibody [28]. The SPR imaging, which utilized the shear force generated within the flow cell, was used to measure the rolling speed of red blood cell [28]. The technique can only extract the information at the interface because the limit of the evanescence field makes it impossible to study in whole cell.…”
Section: Introductionmentioning
confidence: 99%